Dealing with critical challenges in African innovation platforms: Lessons for facilitation - Swaans, Cornelis P.M.; Cullen, Beth; Rooyen, Andre F. van; Adekunle, Adewale; Ngwenya, Hlami; Lema, Zelalem; Nederlof, Suzanne (International Food Policy Research Institute, 2016)
Dynamic innovation processes and differences in interests, capacities, and power present challenges for platform facilitators. Based on group reflection on their own personal experiences facilitating innovation platforms, Chapter 10 (Swaans et al.) discusses key issues that are critical for effective platform facilitation.